Sarcophagidae (Insecta: Diptera) of Saudi Arabia: new records, an updated checklist and a new species - Dawah, Hassan A.; Abdullah, Mohammed A.; Pape, Thomas (Zootaxa, 2024)
As part of a study on the biodiversity of Diptera of south-western Saudi Arabia, a survey of the Diptera fauna of Jazan, Asir and Najran at 10 sites was performed between 2012–2015 mainly using Malaise traps, sweep nets and baited traps. A total of 21 species of Sarcophagidae are recorded and documented with photographs, seven of which represent new country records for Saudi Arabia. Including species with a reliable previous record from Saudi Arabia, the total number of species of Sarcophagidae known from Saudi Arabia now stands at 51. All species of Sarcophagidae recorded from Saudi Arabia are listed, including distributions and the source where species were first recorded. Material studied as part of the project resulted in 16 new country records for other countries. Alusomyia Villeneuve, 1933 is here synonymized with Hoplacephala Macquart, 1834, syn. nov., argued from the presence of four proclinate orbital bristles, the row of strong parafacial setae close to the anteroventral eye-margin, the large gena and the robust habitus compared to most other miltogrammines. The generic synonomy requires the new combinations Hoplacephala transfuga (Villeneuve, 1933), comb. nov. and Hoplacephala turana (Rohdendorf, 1975), comb. nov. Sarcophaga surcoufi Villeneuve, 1913 is synonymized with Engelisca adhamae Lehrer & Abou-Zied, 2008, syn. nov. An appendix authored by Dr J.C. Deeming contains the description of Sarcophaga dawahi Deeming, sp. nov.